Knowledge, Motivation, and Adaptive Behavior: A Framework for Improving Selling Effectiveness - Weitz, Barton A.; Sujan, Harish; Sujan, Mita (Journal of Marketing, 1986)
The authors propose that adaptive selling is influenced by salespeople's knowledge of customer types and sales strategies as well as their motivation to alter the direction of their behavior. Pertinent research in psychology and personal selling is reviewed and specific propositions relating to knowledge, motivation, and adaptive behavior are advanced. On the basis of these propositions, suggestions are made for selecting, training, managing, and compensating salespeople.